Proteomic analysis of Hemoglobin H-Constant Spring (Hb H-CS) erythroblasts - Sriiam,S. (Academic Press Inc., 2015)
Hemoglobin H disease (Hb H) arises through the loss or dysfunction of three of the four alpha globin genes through the co-inheritance of either gross gene deletions or an abnormal hemoglobin which causes a non-deletional loss of α-globin expression. This study sought to investigate erythropoiesis in Hb H-Constant Spring (Hb H-CS) disease, a common form of Hb H disease in Southeast Asia, caused by the inheritance of the Constant Spring variant hemoglobin together with deletion of two of the alpha globin genes. In comparison to normal erythroblasts, Hb H-CS erythroblasts showed reduced cell expansion although no difference in differentiation was observed. Proteomic analysis revealed the increased expression of both chaperone and chaperonin proteins as well as down regulation of proteins regulating apoptosis. Both chaperone and chaperonin mediated folding require ATP, and evidence of increase energy demand was seen in the form of increased expression of enzymes involved in purine biosynthesis and increased levels of reactive oxygen species. A significant increase in apoptosis was seen in Hb H-CS erythroblasts, and the results from the proteomic analysis suggest that this arises at least in part from the consequences of increased folding requirements in the Hb H-CS erythroblast. © 2011 Elsevier Inc..